An “Outside-In” and “Inside-Out” Consideration of Complement in the Multiple Sclerosis Brain: Lessons From Development and Neurodegenerative Diseases - Morgan, B. Paul; Gommerman, Jennifer L.; Ramaglia, Valeria (Frontiers in Cellular Neuroscience, 2021)
The last 15 years have seen an explosion of new findings on the role of complement, a major arm of the immune system, in the central nervous system (CNS) compartment including contributions to migration of cells and synapse elimination during development, detrimental damage of nerve cells in autoimmunity and traumatic injury, and aberrant synapse pruning in neurologic disorders. Activation of the complement system in multiple sclerosis (MS) is typically thought to occur as part of a primary (auto)immune response from the periphery (the outside) against CNS antigens (the inside). However, evidence of local complement production from CNS-resident cells, intracellular complement functions and the more recently discovered role of early complement components in shaping synaptic circuits in the absence of inflammation opens up the possibility that complement-related sequelae may start and finish within the brain itself. In this review, the complement system will be introduced, followed by evidence that implicate complement in shaping the developing, adult and normal ageing CNS as well as its contribution to pathology in neurodegenerative conditions. Discussion of data supporting ‘outside-in’ versus ‘inside-out’ roles of complement in MS will be presented, concluded by thoughts on potential approaches to therapies targeting specific elements of the complement system.